A study on capital structure efficiency measuring on profit before tax / Fauziah Pauzi - Pauzi, Fauziah (2005)
This study aimed to determine and analyze the affect of capital structure on company performance during the period of 1999 - 2003. Two models have been selected to test and analyze the performance (multiple regression analysis and hypothesis testing). The findings have revealed that owner equity and revenue are the most significant independent variables in the variation or changes in PBT.